Ozonation and UV254 nm radiation for the removal of microorganisms and antibiotic resistance genes from urban wastewater - José M. Sousa (2017)
Conventional wastewater treatment has a limited capacity to reduce antibiotic resistant bacteria and genes (ARB&ARG). Tertiary treatment processes are promising solutions, although the transitory inactivation of bacteria may select ARB&ARG. This study aimed at assessing the potential of ozonation and UV254 nm radiation to inactivate cultivable fungal and bacterial populations, and the selected genes 16S rRNA (common to all bacteria), intl1 (common in Gram-negative bacteria) and the ARG vanA, bIa(TEM), sul1 and qnrS. The abundance of the different microbiological parameters per volume of wastewater was reduced by similar to 2 log units for cultivable fungi and 16S rRNA and intll genes, by similar to 3-4 log units, for total heterotrophs, enterobacteria and enterococci, and to values close or below the limits of quantification for ARG, for both processes, after a contact time of 30 min. Yet, most of the cultivable populations, the 16S rRNA and intll genes as well as the ARG, except qnrS after ozonation, reached pre-treatment levels after 3 days storage, suggesting a transitory rather than permanent microbial inactivation. Noticeably, normalization per 16S rRNA gene evidenced an increase of the ARG and intl1 prevalence, mainly after UV254 (nm) treatment. The results suggest that these tertiary treatments may be selecting for ARB&ARG populations.